Website-Based Kaveling Land Marketing Information System in Kampar Programming Regency - Taufit Hidayat (Journal of Engineering Science and Technology Management, 2022)
Land is one of the most valuable assets for human life. In addition to a foothold, land is also a place to earn a living, build houses and assets that can be traded with high value. In obtaining land rights, it is usually done by transferring rights through buying and selling. At this time the marketing of land that has been plotted (plots) for Kampar Regency is still using the conventional method. This conventional method is to market the plots of land by word of mouth. In accordance with current technological developments, marketing is carried out by utilizing print media and social media such as Facebook and Instagram. However, this method is still not effective. Apart from the limited range, the information displayed is mixed with other sales information. To make it easier to reach and clarify marketing information for plots of land, it can be done by utilizing information technology and internet networks. So, information can be accessed by anyone, anytime and anywhere. The creation of a website-based land plot marketing information system in Kampar Regency aims to facilitate communication between sellers and buyers to interact with each other. The purpose of this study is to facilitate communication between sellers and buyers in marketing plots of land through a website. The research method used in this research is the waterfall method. This waterfall method has a sequential flow of software starting from planning, analysis, design, implementation, testing and maintenance. The design of this system uses the Unified Modeling Language (UML). The programming language used is PHP Framework Laravel and MySQL database.